Foreign Block Investors and Participation of Female Directors on the Board - Lee, Sang Cheol; Lee, Yunkeun (Korean Accounting Review, 2023)
This study investigates whether the existence of foreign block investors in the firms affects the participation of female directors on the board of directors. Analyzing 3,540 non-financial firm-year data listed on the Korea Stock Exchange for five years(2014-2018), we find that the participation of female directors on the board increases when foreign block investors exist in the firms. In addition, we find that the relationship between the existence of foreign block investors and participation of female directors on the board is greater in companies managed by non-owner CEO rather than in companies managed by owner-CEO. We also find that the relationship between the existence of foreign block investors and participation of female directors on the board is stronger in companies belonging to a conglomerate business group. These test results support that agency problems play moderating roles on the relationship between the existence of foreign block investors and participation of female directors on the board. Furthermore, analyzing 368 firm-year data with female directors on the board, we find that the existence of foreign block investors increases the monitoring characteristics of female directors such as outside director, expertise, tenure and attendance rate.
Keywords: agency problems; foreign block investors; monitoring characteristics of female directors; participation of female directors on the board